ESTUDO QUÍMICO DE EFLORESCÊNCIAS SALINAS DO SÍTIO ARQUEOLÓGICO TOCA EXÚ DO JURUBEBA DO PARQUE NACIONAL SERRA DA CAPIVARA, PIAUÍ, BRASIL - Farias Filho,Benedito Batista (2017)
Toca Exú do Jurubeba is part of a set of archaeological sites located in the Serra da Capivara National Park (Piauí, Brazil), a region of great world interest due to its archaeological potential, especially rock art. However, rock art is constantly threatened by both natural and anthropic factors. Among the natural salts efflorescences that are deposited on the painted graphics often even concealing them. The present study consisted of the spectroscopic analysis of different saline efflorescence samples of the Serra da Capivara National Park, using examination techniques (optical microscopy and Scanning Electron Microscopy) and analysis (Fourier Transform Infrared and Laser Induced Breakdown Spectroscopy). The analysis allowed to identify at least four different compositions of the samples as a mixture of hydrated calcium oxalate (CaC2O4 H2O) with kaolinite (Al2SiO3(OH)4), gypsum (CaSO4 2H2O), tetrahydrate calcium nitrate (Ca(NO3)2 4H2O) and aluminosilicates in the state of fossilization. The obtained results open the way for the conservation of rock art, initially in the archaeological site under study and can serve as basis for other interventions that may be developed in the region.